Nursery screening for Ganoderma response in oil palm seedlings a manual - Rahmaningsih, Miranti (Techniques in plantation science series ;, 2018)
This manual present methods in a seedling screen for Ganoderma resistance/susceptibility in oil palm (Elaeis guineensis), which means large numbers of seedlings can be screened at the nursery level, and hence allow large numbers to be handled. The results of such selection will give palms, families and populations that can be used in further selection or advancement to commercialization. These then will be grown in a system that also uses appropriate husbandry techniques and biological controls, which in unison prevent or reduce Ganoderma incidence, in other words, in integrated management systems. Topics discussed include: health and safety considerations in the laboratory and nursery; media preparation for in vitro culture of Ganoderma; collecting Ganoderma isolates and culture preparation; preparation of Ganoderma inoculum; nursery inoculation; and scoring response to Ganoderma. Target audiences are students and researchers in agriculture, plant pathologists, plant breeders, growers and end-users interested in the practicalities of oil palm breeding.